Uganda : Technical Assistance Report-Report on the Quarterly National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding compilation of quarterly national accounts statistics. The finalization of the supply and use tables has involved incorporation of significantly revised source data for a number of industries since November 2013, as well as changes in the input data resulting from the implementation of methodological improvements. The Uganda Bureau of Statistics has also made a significant effort to finalize the source data and improve coverage of the economy over the past six months, resulting in revised data for a number of industries. The net impact has been to increase the GDP level by economic activity.